In-plane 2-D patterning of microporous layer by inkjet printing for water management of polymer electrolyte fuel cell. (February 2020) - Bae, Insung; Kim, Bongsoo; Kim, Do-Young; Kim, Hyuk; Oh, Keun-Hwan
Abstract: An appropriate water balance between the conservation of the membrane humidity and the reduction of excess water in the cell remains a key challenge for commercialization of polymer electrolyte fuel cells (PEFCs). Here, we report a microporous layer (MPL) consisting of line patterns with different morphologies by using inkjet printing method, which provides a better water transport pathway not limiting by mass transport for reactant gases to reach the catalyst layer. The pattern-MPL coated on the gas diffusion backing layer (P-GDL) increases the power performance at 50 and 32% RH conditions comparing to commercial one (SGL, 39BC). This result suggests that the in-plane different porous pattern of MPL possesses the significant potential to improve the PEFCs performance with the water balance in the membrane/electrode assembly (MEA). Graphical abstract: Image 1 Highlights: Patterned-gas diffusion layer (P-GDL) is fabricated by inkjet printing method. The P-GDL shows a better water management capability than commercial one. The power performance under 50 and 32% RH conditions is improved.